Fred. Olsen cruise lines: a case study in researching older consumers - Kiddle, Janet (Henry Stewart Talks, 2016)
The case study reviews research conducted on older Fred. Olsen Cruise Line customers. Research focused on consumers’ age-related needs and preferences, and was used to craft a marketing strategy which allowed these customers to experience the brand before even stepping aboard.